Comparison of Sirtuin 3 Levels in ALS and Huntington’s Disease—Differential Effects in Human Tissue Samples vs. Transgenic Mouse Models - Buck, Eva; Bayer, Hanna; Lindenberg, Katrin S.; Hanselmann, Johannes; Pasquarelli, Noemi; Ludolph, Albert C.; Weydt, Patrick; Witting, Anke (Frontiers in Molecular Neuroscience, 2017)
Neurodegenerative diseases are characterized by distinct patterns of neuronal loss. In amyotrophic lateral sclerosis (ALS) upper and lower motoneurons degenerate whereas in Huntington’s disease (HD) medium spiny neurons in the striatum are preferentially affected. Despite these differences the pathophysiological mechanisms and risk factors are remarkably similar. In addition, non-neuronal features, such as weight loss implicate a dysregulation in energy metabolism. Mammalian sirtuins, especially the mitochondrial NAD+ dependent sirtuin 3 (SIRT3), regulate mitochondrial function and aging processes. SIRT3 expression depends on the activity of the metabolic master regulator peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), a modifier of ALS and HD in patients and model organisms. This prompted us to systematically probe Sirt3 mRNA and protein levels in mouse models of ALS and HD and to correlate these with patient tissue levels. We found a selective reduction of Sirt3 mRNA levels and function in the cervical spinal cord of end-stage ALS mice (SOD1G93A). In sharp contrast, a tendency to increased Sirt3 mRNA levels was found in the striatum in HD mice (R6/2). Cultured primary neurons express the highest levels of Sirt3 mRNA. In primary cells from PGC-1α knock-out mice the Sirt3 mRNA levels were highest in astrocytes. In human post mortem tissue increased mRNA and protein levels of Sirt3 were found in the spinal cord in ALS, while Sirt3 levels were unchanged in the human HD striatum. Based on these findings we conclude that SIRT3 mediates the different effects of PGC-1α during the course of transgenic ALS and HD and in the human conditions only partial aspects Sirt3 dysregulation manifest.